Hubungan Dukungan Keluarga Dengan Kualitas Hidup Pasien Gagal Ginjal Kronik Yang Menjalani Terapi Hemodialisis - Lukman Asari (Media Husada Journal Of Nursing Science, 2026)
Hemodialysis is one of the therapies for patients with chronic renal failure, which is a procedure that uses a machine that aims to remove metabolic waste products and correct fluid and electrolyte balance disorders in patients with renal failure. This procedure is carried out continuously throughout life two to four times a week. Patient compliance plays an important role in this procedure which cannot be separated from the role of the family in supporting the Hemodialysis procedure which leads to improving the quality of life of Hemodialysis patients. The purpose of this study was to analyze the relationship between family support and the quality of life of patients in the process of undergoing Hemodialysis. The method used in this research is quantitative method. The number of respondents was 88 patients. Data collection tools using questionnaires, for quality of life using the WHOQOL questionnaire. The results of the Spearman statistical test obtained a value of p = 0.000 or p < 0.05 which indicates the correlation of the two variables. The correlation strength value is 0.685 which means there is a strong relationship. From this study, it is hoped that families can continue to accompany patients while undergoing therapy so that patients do not feel abandoned by their families and can live their days like when they are healthy